2013
DOI: 10.1002/prot.24271
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the design and preparation of nanoscale phospholipid bilayers for its application to solution NMR

Abstract: Despite arduous efforts and recent technological developments structural investigation of integral membrane proteins remains a challenge. The primary deterrents include difficulties with their expression, low inherent solubility and various problems associated with existing membrane mimicking systems. A relatively new class of membrane mimetics, nanodiscs, has been developed as a promising alternative. Although nanodiscs have been proven successful for several biophysical applications, they yet remain to becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…The truncation of MSP1D1 by selective removal of internal helices allowed for the reconstitution of bR and the β-barrel OmpX into nanodiscs as small as 6.3 nm in diameter, making them accessible to multidimensional NMR analysis and higher resolution structure determination (Hagn, Etzkorn, Raschle, & Wagner, 2013). In a related study, C-terminal truncations of MSP down to seven helical repeats rendered improved 15 N TROSY-HSQC spectral quality of integrin a IIB incorporated into nanodiscs, particularly for transmembrane residues (Puthenveetil & Vinogradova, 2013). Interestingly, both studies identified lower size limits for nanodiscs: below a certain MSP length threshold, discs lacked stability or began to form heterogeneous samples containing larger particles.…”
Section: Structural Studiesmentioning
confidence: 97%
“…The truncation of MSP1D1 by selective removal of internal helices allowed for the reconstitution of bR and the β-barrel OmpX into nanodiscs as small as 6.3 nm in diameter, making them accessible to multidimensional NMR analysis and higher resolution structure determination (Hagn, Etzkorn, Raschle, & Wagner, 2013). In a related study, C-terminal truncations of MSP down to seven helical repeats rendered improved 15 N TROSY-HSQC spectral quality of integrin a IIB incorporated into nanodiscs, particularly for transmembrane residues (Puthenveetil & Vinogradova, 2013). Interestingly, both studies identified lower size limits for nanodiscs: below a certain MSP length threshold, discs lacked stability or began to form heterogeneous samples containing larger particles.…”
Section: Structural Studiesmentioning
confidence: 97%
“…A final example for the use of affinity purification in the nanodisc preparation is its combination with nanodisc reconstitution in what is termed on-column reconstitution (Katayama et al 2010, Puthenveetil andVinogradova 2013). Here, either the MSP or the target membrane protein is immobilized on an affinity resin, after which the remaining of the reconstitution components such as lipids and detergents are added.…”
Section: Size Exclusion and Affinity Chromatographymentioning
confidence: 98%
“…This approach allows for a single-step nanodisc reconstitution and purification. Despite the uncertainties in matching optimal reconstitution conditions such as MSP concentration on the column, recent reports have shown it to be feasible for the preparation of monodisperse nanodisc samples (Puthenveetil and Vinogradova 2013).…”
Section: Size Exclusion and Affinity Chromatographymentioning
confidence: 99%
“…Preparing nanodiscs samples for NMR applications are time intensive and requires multiple purifications to separate empty discs from the incorporated ones. We developed a quicker, alternative, on-column method where the protein incorporated discs were formed on the resin either through the bound MSP (approach-1) or the bound target protein (approach-2) [19]. The advantages to this method were several-fold, including reduced preparation time, concomitant separation of empty and incorporated discs and better yields, which collectively improves the quality of our NMR spectrum.…”
Section: Preparation Of Nanodiscsmentioning
confidence: 99%
“…Bacteriorhodopsin, a hepta-helical transmembrane protein, was studied comparatively across different mimetics comprising of micelles, amphipols, and (MSP1D1) nanodiscs [43]. 1 H- 15 N TROSY HSQC spectra of the trans-membrane and cytoplasmic domains of Integrin α IIb spectra was obtained in smaller D7 nanodiscs[19]. YgaP, an E. coli integral membrane protein composed of two transmembrane helices and cytoplasmic Rhodanese domain, was studied in mixed micelles, FC12 micelles, and MSP1D1 nanodiscs.…”
Section: Application Of Nanodiscs For Structural Studies By Solution Nmrmentioning
confidence: 99%